Knowledge and attitude on sexual behaviour among school adolescents - Sah, RB; Ghimire, A; Parajuli, P (Health Renaissance, 2012)
Background: Most of the adolescents of remote areas of Nepal lack the basic knowledge about sex due to which they are suffering from various sex related problems. Objective: To identify the level of knowledge and attitude about sex, sexually transmitted infections (STIs) especially HIV/AIDS and their prevention in adolescents. Methods: This crosssectional study was conducted in various secondary schools of Dhankuta district involving 200 adolescent students aged between 13 to19 years. Collected data was entered in microsoft excel and analysed. Results: Regarding safe sex, most of the students (26%) believe that safe sex is having sex with single partner only and about 13% percent of them had no idea about safe sex. Most of them (94%) think that HIV/AIDs can be transmitted from one person to another person from unsafe sexual contact. Most of the students (93%) believe that avoiding sex with multiple partners could prevent from getting HIV/AIDs. Conclusion: The perception about sexually transmitted diseases varies among school students. Some still had misconception regarding the route and cause of transmission of STI. DOI: http://dx.doi.org/10.3126/hren.v10i3.7140 Health Renaissance; September-December 2012; Vol 10 (No.3);224-228